12 to 16 because all ratios are equivalent
Answer:
x = 6
Step-by-step explanation:
9 / 6 = (2x - 6) / 4 (by the side splitter theorem)
6(2x - 6) = 36
12x - 36 = 36
12x= 72
x = 6
A. (5,7)
b. (5,5)
c. (5,3)
d. (-2,5)
e. (-4,5)
f. (-6,5)
Answer:
Step-by-step explanation:
7
The formula of a midpoint:
![M_{AB}\left(\dfrac{x_A+x_B}{2},\ \dfrac{y_A+y_B}{2}\right)](https://tex.z-dn.net/?f=M_%7BAB%7D%5Cleft%28%5Cdfrac%7Bx_A%2Bx_B%7D%7B2%7D%2C%5C%20%5Cdfrac%7By_A%2By_B%7D%7B2%7D%5Cright%29)
We have:
![M(1.5,\ 1.5)\to x_M=1.5,\ y_M=1.5\\A(5,\ 7)\to x_A=5,\ y_A=7](https://tex.z-dn.net/?f=M%281.5%2C%5C%201.5%29%5Cto%20x_M%3D1.5%2C%5C%20y_M%3D1.5%5C%5CA%285%2C%5C%207%29%5Cto%20x_A%3D5%2C%5C%20y_A%3D7)
Substitute
![\dfrac{5+x_B}{2}=1.5\qquad|\cdot2\\\\5+x_B=3\qquad|-5\\\\x_B=-2\\\\\dfrac{7+y_B}{2}=1.5\qquad|\cdot2\\\\7+y_B=3\qquad|-7\\\\y_B=-4](https://tex.z-dn.net/?f=%5Cdfrac%7B5%2Bx_B%7D%7B2%7D%3D1.5%5Cqquad%7C%5Ccdot2%5C%5C%5C%5C5%2Bx_B%3D3%5Cqquad%7C-5%5C%5C%5C%5Cx_B%3D-2%5C%5C%5C%5C%5Cdfrac%7B7%2By_B%7D%7B2%7D%3D1.5%5Cqquad%7C%5Ccdot2%5C%5C%5C%5C7%2By_B%3D3%5Cqquad%7C-7%5C%5C%5C%5Cy_B%3D-4)
<h3>Answer: (-2, -4)</h3>